On the Strategy for Development of Western Regions of PRC - Мұқaметхaнұлы Н.; Серғaзы Е. (Journal of Oriental Studies, 2018)
In the first part of the article, the socio-political reasons for the implementation the development strategy of the Western regions of the PRC, the time and stages of implementing the strategy are determined. The projects of the PRC government on development of the Western regions, financial issues and general provisions of the project implementation are considered. In the second part of the article, the development policy of Xinjiang is considered as part of the development strategy of the Western regions, legislative acts, plans, amounts of funding, the goals pursued and the results of development to date. The article notes that the decrease in the water volume of Transboundary Rivers is unprofitable for Kazakhstan, nevertheless, that the development of the Western regions of the PRC, especially the social and economic development of Xinjiang, is very beneficial for Kazakhstan.In the first part of the article, the socio-political reasons for the implementation the development strategy of the Western regions of the PRC, the time and stages of implementing the strategy are determined. The projects of the PRC government on development of the Western regions, financial issues and general provisions of the project implementation are considered. In the second part of the article, the development policy of Xinjiang is considered as part of the development strategy of the Western regions, legislative acts, plans, amounts of funding, the goals pursued and the results of development to date. The article notes that the decrease in the water volume of Transboundary Rivers is unprofitable for Kazakhstan, nevertheless, that the development of the Western regions of the PRC, especially the social and economic development of Xinjiang, is very beneficial for Kazakhstan.